1998
DOI: 10.1177/0961463x98007002008
|View full text |Cite
|
Sign up to set email alerts
|

Time Creation in Travelling

Abstract: This paper deals with long-term budget travelling from different time perspectives. Narratives of travel, given by women backpackers and interpreted through `time lenses', lead to an analysis of the journey as an individualized time-space in which the traveller regains control of her own time and movement. It is argued that this control, sensed as `freedom', opens up both mind and body to a complexity of different time experiences. These vary depending on context and speed of movement. Thus, the long-term jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…There are also strong linkages with the concept of travel time as a gift and co-production with other travellers en route (Jain & Lyons, 2007). In some contexts this might lead to situations where the traveller structures his or her own time and space, for example in relation to backpacking (Elsrud, 1998). Authors such as Dann (1994) in discussing train tourism, Halsall (2001) in a study of tram trains and Schiefelbusch, Jain, Schâfer and Müller (2007) in relation to integrated public transport point to the inherent value of the travel experience; i.e.…”
Section: Mode Of Transport and Travel Experiencementioning
confidence: 96%
“…There are also strong linkages with the concept of travel time as a gift and co-production with other travellers en route (Jain & Lyons, 2007). In some contexts this might lead to situations where the traveller structures his or her own time and space, for example in relation to backpacking (Elsrud, 1998). Authors such as Dann (1994) in discussing train tourism, Halsall (2001) in a study of tram trains and Schiefelbusch, Jain, Schâfer and Müller (2007) in relation to integrated public transport point to the inherent value of the travel experience; i.e.…”
Section: Mode Of Transport and Travel Experiencementioning
confidence: 96%
“…Poor connection of transport modes at the railway stations may result in inefficient station operation and undesirable service, which may stop patrons from using transit systems (Mbatta, Sando, & Moses, 2008). Finally, the importance of ride comfort generally and seat comfort in particular is supported by Elsrud (1998) who claimed that the railway tourism experience that is largely remembered predominantly comprises visual observation throughout the specially designed train route, with the train carriages offering comfortable seating. It is, therefore, concluded that the provision of heritage railway attractions, both on-train and off-train, represents an essential and important component of the railway tourism experience, whereas the smoothness and comfort of a rail journey play a supporting role in enhancing RTA.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 97%
“…This often raises the notion of the professionalisation of the gap year, whereby experiences from travel help to build skills to enable young people to compete better in the market place (Simpson 2005;Lyons et al 2012). A gap year can encourage global citizenry, broaden the mind (Simpson 2005), promote the discovery of cross-cultural experiences to help build the travellers identity (Jones 2005;Hirschorn and Hefferon 2013), autonomy (Brown 2009;Christofi and Thompson 2007), self-efficiency (Cushner and Karim 2004), time satisfaction (Elsrud 1998;Montuori and Fahim 2004) and creativity (Maddux and Galinsky 2009). It can also serve as a way to discover the self and develop interests and ambitions, values and strengths (Lyons et al 2012).…”
mentioning
confidence: 97%